Let's expand the expression \((−x^2 − 9x − 10)(x^2 − x − 1)\) and express it in standard form.
-
Distributing each term in \((−x^2 − 9x − 10)\) to each term in \((x^2 − x − 1)\):
\[ (-x^2)(x^2) + (-x^2)(-x) + (-x^2)(-1) + (-9x)(x^2) + (-9x)(-x) + (-9x)(-1) + (-10)(x^2) + (-10)(-x) + (-10)(-1) \]
-
Calculating each multiplication:
- \( -x^2 \cdot x^2 = -x^4 \)
- \( -x^2 \cdot -x = x^3 \)
- \( -x^2 \cdot -1 = x^2 \)
- \( -9x \cdot x^2 = -9x^3 \)
- \( -9x \cdot -x = 9x^2 \)
- \( -9x \cdot -1 = 9x \)
- \( -10 \cdot x^2 = -10x^2 \)
- \( -10 \cdot -x = 10x \)
- \( -10 \cdot -1 = 10 \)
-
Now we combine all of these products: \[ -x^4 + x^3 + x^2 - 9x^3 + 9x^2 + 9x - 10x^2 + 10x + 10 \]
-
Combine like terms:
- Combine \(x^3\) terms: \(x^3 - 9x^3 = -8x^3\)
- Combine \(x^2\) terms: \(x^2 + 9x^2 - 10x^2 = 0\)
- Combine \(x\) terms: \(9x + 10x = 19x\)
- The constant term is \(10\).
-
Thus, we get: \[ -x^4 - 8x^3 + 19x + 10 \]
Putting it all together, the final expression in standard form is: \[ \boxed{-x^4 - 8x^3 + 19x + 10} \]